Transformasi Digital Industri Perhotelan: Studi pada Industri Perhotelan di Daerah Istimewa Jogyakarta - Prihanto, J. Johny Natu; Siahaan, Dian (Manajemen Bisnis Kompetensi, 2018)
Hotel industry in Indonesia face the rapid uses if internet and digitalization as both challenges and opportunities. The internet and digitalization change the hotel industri’s business model and customer behavior. This led market turbulence that forced the hotel industry leaders to reconfigure the capabilities they have. Research was carried out in Jogyakarta. Jogyakarta was chosen becouse it is the second largest tourist destination in Indonesia. Respondents of this study were the genaral managers or the owners of the the hotel industry. The analysis technique used structural equation model (SEM) with the partial least square (PLS) approach. The results of this study show that hotel industry leaders must rethink the dimension of customer experience, internal operation, and new business model. The company must have cohesive strategy in integrating digital and physical elements in order to be able to transform its business model and set direction for the entire industry. Hotel industry leaders must also focus on two complementary activities: sharpening customer value proposition and transforming their operating models using digital technology to interact and collaborate with customer. From the managerial aspect this study contributes that managers must focus on factors such as digital market capabilities, digital leadership capabilities, and digital technology capabilities that determine the succes of digital transformation in order to build and increase customer engagement. Keywords: market capabilities, leadership capabilities, digital capabilities, sustainable digital transformation, customer engagement.